The Myth of Beauty: The Efforts of The “Unej Cantik” Community to Achieve Ideal Beauty - Thalia, Vena; Sair, Abdus; Elanda, Yelly; Alie, Azizah; Sholahudin, Umar (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This article analyzes the myth of beauty within the “UNEJ Cantik” community, focusing on its members' efforts to achieve the ideal concept of beauty. The research highlights the collective and horizontal interactions among community members in shaping beauty standards, a perspective that is less commonly discussed compared to studies emphasizing the role of individuals or influencers in establishing beauty norms. Using the netnography method, data were collected through observations and in-depth interviews with community members, comprising 10 core informants, 5 additional informants, and 2 account administrators. The findings reveal that the community's ideal beauty standards include glowing skin, a slim body, straight hair, and natural makeup. These standards are influenced by three main contexts: mass media (including social media), Dutch colonial heritage, and the local Pandhalungan culture. To achieve these standards, community members engage in various practices such as using skincare products, undergoing whitening injections, getting hair treatments, and getting eyelash extensions. This phenomenon reflects the tension between students' rational aspirations and the exploitation by the beauty market, as well as the clash between local values and global aesthetics. Thus, this study aims to foster critical awareness of the social pressures arising from the homogenization of modern beauty standards.